Banal and everyday (inter)nationalism: French and Italian anarchist exiles in London, 1870s–1914. Issue 1 (28th October 2022) - Bantman, Constance; Di Paola, Pietro
Abstract: This article explores the anarchists' multilayered theoretical and practical engagement with the concepts and performance of nations, nationalism and national belonging, by applying the frameworks of banal nationalism (understood as an ideology) and everyday nationhood (the daily practices in which nation and nationhood are enacted) as analytical categories, to investigate the Italian and French anarchist exile groups in London between 1870 and 1914. Adopting these theoretical categories proves fruitful in probing the anarchists' perception and enactment of the idea of nation and national belonging, contributing to the literature on the relationship between pre‐1914 socialist movements and (inter)nationalism and highlighting the specificity of anarchism therein. Using Fox and Miller‐Idriss's four categories of everyday nationhood, we show that while the anarchists explicitly subverted the everyday performance of nationhood, redeploying it along internationalist lines, some forms of attachment to the national did endure and were in fact not always contradictory with anarchist internationalism. Looking at the exilic rituals of this intensely diasporic group thus complicates the simplistic but still pervasive view of a monolithic ideological internationalism and rejection of the national on the part of anarchists.